2014
DOI: 10.1016/j.virol.2014.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Infectious cDNA clones of the crinivirus Tomato chlorosis virus are competent for systemic plant infection and whitefly-transmission

Abstract: Tomato chlorosis virus (ToCV) (genus Crinivirus, family Closteroviridae) causes important emergent diseases in tomato and other solanaceous crops. ToCV is not transmitted mechanically and is naturally transmitted by whiteflies. The ToCV genome consists of two molecules of linear, positive-sense RNA encapsidated into long flexuous virions. We present the construction of full-length cDNA clones of the ToCV genome (RNA1 and RNA2) fused to the SP6 RNA polymerase promoter and under the control of the CaMV 35S promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…Furthermore, Northern blot analyses were conducted using DIG-labelled specific RNA probes for RNA1 (566 nt within the P22 gene) and RNA2 (698 bp within the CP gene), which were synthesized using DIG RNA labelling mix (Roche) with specific primers P26/P27 and P28/P29 (Table S1). Consistent with LIYV (Klaassen et al, 1996;Wang et al, 2009), LCV (Mongkolsiriwattana et al, 2011) and ToCV (Orílio et al, 2014), CCYV RNA1 showed strong replication at 1-day post-infection (dpi) (Fig. 2c).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, Northern blot analyses were conducted using DIG-labelled specific RNA probes for RNA1 (566 nt within the P22 gene) and RNA2 (698 bp within the CP gene), which were synthesized using DIG RNA labelling mix (Roche) with specific primers P26/P27 and P28/P29 (Table S1). Consistent with LIYV (Klaassen et al, 1996;Wang et al, 2009), LCV (Mongkolsiriwattana et al, 2011) and ToCV (Orílio et al, 2014), CCYV RNA1 showed strong replication at 1-day post-infection (dpi) (Fig. 2c).…”
supporting
confidence: 64%
“…Unlike previously reported crinivirus infectious clones of LIYV, LCV and ToCV, which are fully active in the host plants after grafting or virion transmission by whiteflies from agroinfected N. benthamiana plants (Wang et al, 2009;Chen et al, 2012;Orílio et al, 2014), our CCYV infectious clone successfully established direct infection in the host plant C. sativus, as well as N. benthamiana , indicating a potentially wide range of host applications. To our knowledge, our infectious clone of CCYV represents the first report of successful infection of a crinivirus in the natural host plant and in N. benthamiana.…”
mentioning
confidence: 52%
“…The p22 protein encoded in the RNA1, as well as the major (CP) and minor (CPm) coat proteins encoded in the RNA2 of ToCV are implicated as RNA silencing suppressors (RSS) (14). Until now, the CP is the only viral protein being detected in ToCV-infected tomato plants (15). In vitro assays demonstrated that the p22 protein is bound preferentially to the long dsRNAs, thus protecting these dsRNAs from dicer cleavage (16).…”
mentioning
confidence: 99%
“…The full-length cDNAs of ToCV RNA1 and 2 were cloned under a double 35S promoter in the binary vector pCass-RZ (18) to produce the two constructs pCaToCR1 and pCa-ToCR2 for ToCV RNA1 and RNA2, respectively. Biological activity of the constructs pCa-ToCR1 and pCa-ToCR2 was demonstrated through agroinfection of N. benthamiana plants according to reported protocols (15).…”
mentioning
confidence: 99%
“…Data on the function of crinivirus P59 and P9 are limited due to the lack of an efficient reverse genetics system. To date, several full-length infectious clones of criniviruses have been constructed and will promote the study of crinivirus genotypes as well as the interactions of P59 and P9 in planta [14][15][16].…”
mentioning
confidence: 99%